Anticancer Activity of Amb4269951, a Choline Transporter-Like Protein 1 Inhibitor, in Human Glioma Cells - Saiichiro Watanabe; Nozomi Nishijima; Kaho Hirai; Kaoru Shibata; Akane Hase; Tsuyoshi Yamanaka; Masato Inazu (MDPI AG, 2020)
Choline transporter-like protein 1 (CTL1) is highly expressed in glioma cells, and inhibition of CTL1 function induces apoptotic cell death. Therefore, CTL1 is a potential target molecule for glioma therapy. Here, we investigated the therapeutic mechanism underlying the antitumor effects of Amb4269951, a recently discovered novel CTL1 inhibitor, in the human glioma cell line U251MG, and evaluated its in vivo effects in a mouse xenograft model. Amb4269951 inhibited choline uptake and cell viability and increased caspase-3/7 activity. CTL1-mediated choline uptake is associated with cell viability, and the functional inhibition of CTL1 by Amb4269951 may promote apoptotic cell death via ceramide-induced suppression of the expression of survivin, an apoptotic inhibitory factor. Finally, Amb4269951 demonstrated an antitumor effect in a mice xenograft model by significantly inhibiting tumor growth without any weight loss. Amb4269951 is the lead compound in the treatment of glioma and exhibits a novel therapeutic mechanism. These results may lead to the development of novel anticancer drugs targeting the choline transporter CTL1, which has a different mechanism of action than conventional anticancer drugs against gliomas.